2018
DOI: 10.1016/j.ijscr.2018.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic abdominal wall seroma with Doxycycline sclerotherapy using a Negative Pressure Wound Therapy System KCI-V.A.C.Ulta™—A case report

Abstract: HighlightsSeroma is a common and challenging post-operative complication for both surgeons and patients.Doxycycline can be a simple, safe and effective method for resolution of chronic seroma.Negative Pressure Wound Therapy System can induce seroma cavity collapse and surface adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…For seromas refractory to simple drainage, chemical or mechanical sclerotherapy have both been described. Chemical sclerosing agents including talc, tetracycline, doxycycline, ethanol, erythromycin, fibrin glue, and povidone/iodine have all been used with high success rates and few complications; however, only small case series exist in the literature [16,17] . Lehr and Schuricht [18] described endoscopic ablation of the inner lining of the seroma using the argon beam in extreme cases.…”
Section: Seromamentioning
confidence: 99%
“…For seromas refractory to simple drainage, chemical or mechanical sclerotherapy have both been described. Chemical sclerosing agents including talc, tetracycline, doxycycline, ethanol, erythromycin, fibrin glue, and povidone/iodine have all been used with high success rates and few complications; however, only small case series exist in the literature [16,17] . Lehr and Schuricht [18] described endoscopic ablation of the inner lining of the seroma using the argon beam in extreme cases.…”
Section: Seromamentioning
confidence: 99%
“…In 1983, Nichter et al (20) preconised the use of tetracycline sclerotherapy for the treatment of persistent seromas. More recently, a case report described the use of doxycycline as another sclerosing agent (21). In 2006, Saeb-Parsy et al (10) described the application of talc in an 8-month recurrent chronic seroma after breast surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The use of sclerotherapy in the management of seromas has been reported in small-scale studies and case reports, and has shown strong success with minimal complications. 3 Any improvement in our ability to treat this challenging complication is of great importance.…”
Section: Introductionmentioning
confidence: 99%